Concomitant supernumerary tooth with partial anodontia in the mandibular anterior region: A nonsyndromic rare condition - Madhuri Alankar Sawai (Wolters Kluwer Medknow Publications, 2016)
Partial anodontia is the failure of one or more teeth to develop. It is quite common in the permanent dentition. The third molars, mandibular second premolars, and maxillary lateral incisors are the most common teeth to be congenitally missing. However, it is rare in the mandibular arch. A combined occurrence of a supernumerary tooth with hypodontia is still rarer, especially when it occurs in the same dental arch and in a nonsyndromic situation. Only a few cases of this condition have been reported in the dental literature. The case reported here describes one such rare occurrence.